A Canadian Isolate of Hepatitis D (delta) Virus - Véronique Poisson; Daniel B Ménard; Éric Frost; Jean-Pierre Perreault (Canadian Journal of Gastroenterology)
HepatitisD(delta) virus (HDV) is an infectious agent that propagates in hepatocytes only in the presence of hepatitis B virus, causing fulminant or chronic hepatitis with liver cirrhosis. HDV is a 36 nm particle that includes a circular RNA genome of 1.7 kilobases with an extensive internal complementary that allows it to fold into a rod-like structure. The relationships among genotypes, sequence variability, geographical distribution and disease severity of HDV remain unknown. Consequently, in the present study, the complete nucleotide sequence of anHDVisolated from a Canadian patient was determined. The viral RNA from serum was amplified using reverse transcription coupled to polymerase chain reaction amplification. The resulting complementary DNA was cloned and sequenced. Sequence analysis revealed that this new isolate contained 1672 nucleotides corresponding to genotype 1, which has a worldwide distribution. Sequencing of four independent clones revealed 17 substitutions, corresponding to an overall sequence variability of 1%. Surprisingly, seven mutations were found in the 48-nucleotide region located between the two highly conserved self-catalytic motifs. This is the first demonstration that many substitutions are identified in this region of HDV, and prompts the present authors to define it as a hypervariable region.